Analisis Pengaruh Kecepatan Aliran Udara Terhadap Penurunan Temperatur Efektif Pada Alat Simulasi Ventilasi Tambang Bawah Tanah - Dhoni Syaputra; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. In underground mines the ventilation system is very important in terms of meeting the air respiratory needs of workers, cleaning dirty air, toxic gases, concentrating dust, regulating heat and humidity in the mine. The problem that often occurs in underground mining, especially in Sawahlunto is the high temperature temperature on the workers' mining front, so that the safety and comfort of the workers is no longer in line with the rules set by the Kepmen 555K/MPE/1995.To meet the standards of effective air and temperature requirements at the mining front, the author tries to conduct an experiment with an underground mine ventilation simulation tool located at the FT .UNP mine laboratory, the experiment was carried out by flowing different air flow velocities using suction fan, blow fan 16 ", fan blows 20" variation of 3 speed without addition of water and fan blows 20 "variation 3 speed by setting the addition of minimum, medium and Maximum water to the underground mine ventilation simulation tool. Based on the data obtained at the measurement points using an Anemometer and Digital Sling Psychometer, the conclusion is that with an average increase in air flow rate of 30%, it can reduce the temperature of the effective temperature by 15%. In this study, the lowest temperature is at point B, in experiments using a 20 "high speed blow fan with setting the maximum water addition, ie 15.40 C (down from 19.80 C, or 28.5% using fan type and the same speed, but without the addition of water) with air flow velocity of 5.22 m / sec, (up from 3.20 m / sec, or 63% using the fan type and the same speed, but without additions water)  Keywords: Ventilation System, Temperature, Difference in Air Flow Speed, Water Addition Setting, Effective Temperature